Principles of Islamic Education - Raysha Rahmani Fabillah; Sindi Umami; Alihan Satra (Advances In Education Journal, 2025)
Islamic Education represents a deliberate and structured effort to guide learners in developing their potential holistically as servants of Allah who fulfill the role of khalifah (steward) on earth. Contemporary Islamic education faces fundamental challenges, particularly the dichotomy between religious and secular knowledge and formalism in moral education. This article aims to clarify the philosophical foundations of Islamic education principles, formulate the core principles centered on Tauhid (Islamic monotheism), and systematically classify them into Fundamental, Methodological, and Operational categories. Through philosophical approach and literature review, this study demonstrates that Islamic education principles form an integrated framework where Tauhid serves as the central axis integrating all aspects of education. The findings reveal that sustainable implementation of these principles can overcome the fragmentation of knowledge and address formalism in character development. This systematic classification provides a clear reference framework for educational institutions, policymakers, and educators in implementing Islamic education more effectively, humanely, and in accordance with contemporary developments.